Fluktuasi Harga Pangan Dan Pengaruhnya Terhadap Inflasi Di Kota Padang, Provinsi Sumatera Barat - Putri, Mega Amelia; Afrizal, Roni; Arnayulis, Arnayulis; Alfikri, Alfikri (Agropross : National Conference Proceedings of Agriculture, 2022)
One of the contributors to inflation in Padang City comes from the food and/or food ingredients subgroup. In this subgroup, the variable that dominates the inflation rate is food prices. Unstable inflation conditions will have an impact on the economy of a region. The purpose of the study was to identify the development of food prices in the city of Padang and to analyze the effect of food price fluctuations on inflation in the city of Padang. Data for the period January 2018 to December 2021 are used for descriptive analysis and vector autoregressive modeling (VAR/VECM). The variables used are the prices of rice, red chilies, cooking oil, broiler eggs, broiler meat, and granulated sugar. will be analyzed its effect on inflation in the city of Padang. The condition of food prices shows a fluctuating trend. The analysis results show that in the short term cointegration occurs between variables. In the long term, the prices of rice, red chilies, broiler eggs, and chicken meat have a significant effect on inflation in the city of Padang. The projection results for the next 24 years show that the most significant contribution of variance is dominated by the inflation variable (53.69%). The most significant strategic food commodity in explaining the inflation diversity of Padang City is red chili (22.99%) and rice (16.76%). The rest (6.56%) is explained by other commodities' price variables. The contribution of food prices identified as having an impact on inflation in the City of Padang should be the focus of attention of the local government in setting trade regulations in the future.